2014
DOI: 10.1590/s1517-83822014000300019
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological potential of Clostridium butyricum bacteria

Abstract: In response to demand from industry for microorganisms with auspicious biotechnological potential, a worldwide interest has developed in bacteria and fungi isolation. Microorganisms of interesting metabolic properties include non-pathogenic bacteria of the genus Clostridium, particularly C. acetobutylicum, C. butyricum and C. pasteurianum. A well-known property of C. butyricum is their ability to produce butyric acid, as well as effectively convert glycerol to 1,3-propanediol (38.2 g/L). A conversion rate of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…PA is mainly produced by Propionibacterium, as well as Clostridium propionicum and Selenomonas ruminantium [ 13 ], which is suppressed in lower pH conditions below 4.5 [ 36 ]. BA, which is the result of amino acids fermentation and leads to nutrition losses and is an indicator of bad preservation, is mainly produced by Clostridium butyrate and suppressed in lower pH conditions [ 37 ]. HN3-N, the proportion of which was related to proteolysis activity in the ensiling process and negatively related to the voluntary intake of silage [ 38 ], was caused by the proliferation of Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…PA is mainly produced by Propionibacterium, as well as Clostridium propionicum and Selenomonas ruminantium [ 13 ], which is suppressed in lower pH conditions below 4.5 [ 36 ]. BA, which is the result of amino acids fermentation and leads to nutrition losses and is an indicator of bad preservation, is mainly produced by Clostridium butyrate and suppressed in lower pH conditions [ 37 ]. HN3-N, the proportion of which was related to proteolysis activity in the ensiling process and negatively related to the voluntary intake of silage [ 38 ], was caused by the proliferation of Clostridium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotics assisted in stabilizing beneficial gut microbes, increasing the digestion of nutrients, stabilizing beneficial gut microbes, enhancing immuno-modulation, and increasing the intestinal villi length, thereby increasing the surface area of absorption, and improving bird health [ 12 , 32 ]. The growth promoting effect observed in the probiotic mixture group (G4) could be attributed to the synergistic actions of C. butyricum and S. cerevisiae , which contained mannan oligosaccharides (derived from the cell wall of S. cerevisiae ; affect through fermentation of different sugars and synthesis of enzymes that can help in better utilization of nutrients and act as a substrate for C. butyricum in the gut of broilers) [ 18 , 33 ]. In addition, probiotic bacteria can protect against several harmful pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the high abundance of Clostridium could also be due to their ability to modify or utilize such extracellular matrix (Hentschel et al 2012 ). Interestingly, many members of the genus Clostridium , are also known for their fermentation capacity and antibacterial properties (Szymanowska-Powalowska et al 2014 ). However, on the contrary, studies on the marine sponges have also shown the increase in the abundance of Clostridium due to environmental stresses or toxic chemicals (Tian et al 2014 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%